STUDY OF THE PROPERTIES OF NON-WOVEN THERMALLY BONDED MATERIALS (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
The influence of the main technological parameters and the content of modifiers and plasticizers on the physical and mechanical properties of non-woven thermally bonded materials has been studied. The optimal values for the content of binder, plasticizer, modifier, catalyst and thermal bonding conditions have been established